新中两地上海方言语码转换现象及其动因探讨 = Study of the code-switching phenomenon of the Shanghai dialect in Singapore and Shanghai - 朱照敏 Zhu, Zhaomin (2011)
本文重点介绍在上海和新加坡，他们的第一语言是上海话的年轻人就业的语码转换的现象。上海话曾经在中国享有重要地位。因此，这是值得探讨的语码转换的现象，在近几年的地方。我的目标是在上海比较，新加坡的现象，并找出根本原因。首先，我将介绍上海方言的形成，其基本特征，它的历史发展。然后，我会做出对上海方言和普通话（标准中）的比较。在下一节中，我将会出现20至40岁来自上海和新加坡的第一语言是上海话我的抽样访谈20人。我会给我的意见的基础上所记录的语码转换实例和社会环境如何影响了方言的分析。This paper focuses on the code-switching phenomenon employed by young people in Shanghai and Singapore, whose first language is the Shanghai dialect. The Shanghai dialect once enjoyed an important status in China. It is thus worth exploring its code-switching phenomenon that has taken place in recent years. My aim is to compare this phenomenon in Shanghai to that in Singapore, and to find out the underlying motivation. First, I will introduce the formation of the Shanghai dialect, its basic characteristics, and its historical development. I will then make a comparison between Shanghai dialect and Putonghua (Standard Chinese). In the next section, I will present my sample interviews with 20 people aged between 20 and 40 from Shanghai and Singapore whose first language is the Shanghai dialect. I will give my observations based on the recorded code-switching instances and analysis of how the social environment has influenced a dialect.